IN VIVO EVALUATION OF THE ANTIPLASMODIAL EFFICACY OF MANGIFERA INDICA LEAF EXTRACT IN PLASMODIUM BERGHEI-INFECTED MICE - Bassa, Obed Yakubu; Fodeke, Henena; Abdullahi, Maryam Mama (FUDMA JOURNAL OF SCIENCES, 2024)
The menace of malaria has been and is still one of the most devastating in the world. Chemotherapy, the main control strategy, is under threat as the parasite develops resistance to currently available antimalarial drugs. Therefore, the search for new compounds with novel mechanisms of action and targets to treat malaria is inevitable as nature is a constantly evolving source of compounds with medical importance. The present study aims to investigate the toxicological and in vivo antiplasmodial effects of Mangifera indica extract on albino mice infected with Plasmodium berghei (ANKA). Swiss albino mice (15-25g), chloroquine sensitive P. berghei and Fresh M.indica leaves were collected, air dried, ethanol extract obtained and used for the study. The modified Lorke method was adopted to determine acute toxicity, with 3 groups of mice intraperitoneally administered varying doses of the extracts in 2 phases. The malaria parasite plasmodium berghei was inoculated into the apparently healthy Swiss albino mice. The curative evaluation of grouped mice used at various concentrations (150mg/kg, 300mg/kg, and 1200mg/kg) alongside negative (distilled water) and positive (10mg/kg chloroquine) controls were performed. The parameters of body weight, packed cell volume and parasitemia were determined using Ranes’ and Peters test. No toxicity was observed at a maximum dose of 4000mg/Kg. A four-day curative test was performed with mice inoculated intraperitoneally with 1x107 parasitized erythrocytes per mL. Chloroquine (10mg/kg) and distilled water (untreated) were administered as positive and negative controls, respectively, while the plant extract concentrations of 150mg/kg, 300mg/kg and 1200mg/kg were administered orally to the...